Estimates of the supremum distribution for a certain class of random processes - Buldygin, V. V.; Kozachenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Exponential estimates of the “tails” of supremum distributions are obtained for a certain class of pre-Gaussian random processes. The results obtained are applied to the quadratic forms of Gaussian processes and to processes representable as stochastic integrals of processes with independent increments.